Solving Coupled Fractional Differential Equations Using Differential Transform Method. - et. al., Mridula Purohit, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the solution of coupled equations which are of fractional order using differential transform method. In this paper we extend the scope of differential transform method to system of fractional differential equations so that we get the analytical solutions. The coupled fractional differential equations of a physical system, namely, coupled fractional oscillator with some applications is given via differential transform method. Here we introduce the solution of coupled oscillation of equal fractional order which can be enhanced to unequal fractional order.